Pengaruh Pemasaran dan FoMo: Sebuah Studi tentang Bagaimana Pengaruh Influencer Mempengaruhi Keputusan Pembelian Labubu Melalui FoMo pada Kalangan Gen Z di Surabaya - Revalya Rachminda; Rizky Dermawan; Ratih Mukti Azhar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study explores the interconnections among influencer marketing, FoMo, and purchase decisions, focusing on Gen Z consumers in Surabaya. This study examines the direct effect of influencer marketing on the online purchasing decisions of Labubu and explores the mediating role of FOMO in this relationship. The research method used is quantitative. The sampling technique employed is non-probability sampling with purposive sampling and tested using the SmartPLS application with PLS-based SEM method. The findings reveal that influencer marketing has a positive and significant effect on purchase decisions. Additionally, FoMO is identified as a crucial mediating variable that strengthens the impact of influencer marketing on purchase decisions. This study contributes to the understanding of consumer behavior by highlighting the mediating role of FoMO in the relationship between influencer marketing and online purchase decisions. This is done through their marketing strategies by leveraging influencer marketing combined with psychological triggers, namely FoMO, which effectively influence and enhance purchase decisions among consumers, especially Generation Z. This suggests that marketing strategies through influencers can enhance FOMO behavior among Gen Z consumers, thereby encouraging them to make online purchases.